Introduction to Sociology - O'Donnell, Mike. (Walton-on-Thames : Nelson, 1997)
The fourth edition of Introduction to Sociology is an essential textbook for all students of A and AS-Level Sociology, and is also relevant for students in higher education. Key sociological concepts are introduced and defined.
Previous ed.: published as A new introduction to sociology. 1992.
Includes bibliographical references (p. 650-656) and index.
Keywords: Sociology; Sociology -- Problems, exercises, etc; Society